2005
DOI: 10.1177/104063870501700317
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Liposarcoma in a Dog

Abstract: Abstract.A 9-year-old, female Mongrel dog was presented for posterior hindlimb weakness, inability to stand, and pain in the lumbosacral and pelvic regions. Radiography revealed a lytic lesion extending from L5 to L6 to the ilium. At necropsy, an 8 ϫ 2 to 3.2 ϫ 3 cm, irregular, white, firm mass was identified extending from the left dorsolateral aspect of the L6 vertebrae to the sacrum, crossing the sacroiliac joint to the ilium, and reaching the acetabulum without affecting the joint cartilage. Tumor masses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 12 publications
3
32
0
Order By: Relevance
“…Expression of vimentin, confirming the mesenchymal origin, and S-100 protein, suggestive of liposarcoma, have previously been described in canine liposarcoma (Wang and others 2005). The macroscopic findings suggested that the primary site of the liposarcoma in this case was the marrow of the right radius, but a periosteal liposarcoma must be considered as a differential diagnosis (Thompson and Pool 2002).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Expression of vimentin, confirming the mesenchymal origin, and S-100 protein, suggestive of liposarcoma, have previously been described in canine liposarcoma (Wang and others 2005). The macroscopic findings suggested that the primary site of the liposarcoma in this case was the marrow of the right radius, but a periosteal liposarcoma must be considered as a differential diagnosis (Thompson and Pool 2002).…”
supporting
confidence: 69%
“…In human beings, a prevalence of 0.03 per cent among all bone neoplasms has been reported (Mirra and others 1989). It arises from adipocyte precursors in the marrow cavity and has been observed in the long bones or lumbar vertebrae of dogs (Brodey and Riser 1966, Davis and others 1974, Nielsen 1976, Wang and others 2005), the mandible of a ferret (Fuentealba and Blue-McLendon 1995) and the metacarpus of a kudu (Raubenheimer and others 1990). Histologically, liposarcomas of bone closely resemble their soft tissue counterpart (Brodey and Riser 1966, Thompson and Pool 2002).…”
mentioning
confidence: 99%
“…The microscopical features of tumor cells together with Oil Red O positivevacuoles and Alcian blue positive-stroma verified the first case of the myxoid variant of liposarcoma in a cat. Vimentin and S-100 immunolabeling are suggestive of liposarcoma (11). Our case showed only vimentin immunolabeling, but was negative for S-100.…”
Section: Bir Kedide Miksoid Liposarkommentioning
confidence: 79%
“…Liposarcomas are rare neoplasms in domestic animals, but have been reported to occur in many species [1,4,5,[7][8][9][11][12][13]. In Herpestidae animals, the neoplasms have seldom been reported and, to our knowledge, their occurrence has not been documented for meerkats so far [10].…”
mentioning
confidence: 83%